2023
DOI: 10.3389/fphar.2023.1325871
|View full text |Cite
|
Sign up to set email alerts
|

The current view of potentially inappropriate medications (PIMs) among older adults in Saudi Arabia: a systematic review

Fawaz M. Alotaibi

Abstract: Introduction: Potentially inappropriate medications PIMs are common among elderly population and becoming a global health issue. It has been associated with negative health consequences like preventable adverse drug reactions, hospitalization and mortality.Objectives: To investigate the most commonly potentially inappropriate medications in older adults in Saudi Arabia. Additionally, we aim to gain insights into the typical healthcare settings where healthcare providers offer services related to PIMs.Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(64 reference statements)
0
0
0
Order By: Relevance
“…This study concluded that this high percentage needs additional research to figure out the reasons behind the variation across demographics and different health care settings. 12 Another study in Saudi Arabia conducted in 2022, aimed to analyze the relationship between the PIMs and frailty among inpatient older adults. This study found out that there is a strong relation between PIMs and frail older adults with multiple disorders.…”
Section: Introductionmentioning
confidence: 99%
“…This study concluded that this high percentage needs additional research to figure out the reasons behind the variation across demographics and different health care settings. 12 Another study in Saudi Arabia conducted in 2022, aimed to analyze the relationship between the PIMs and frailty among inpatient older adults. This study found out that there is a strong relation between PIMs and frail older adults with multiple disorders.…”
Section: Introductionmentioning
confidence: 99%